Phylogenetic Responses of Marine Free-Living Bacterial Community to Phaeocystis globosa Bloom in Beibu Gulf, China - Li, Nan; Zhao, Huaxian; Jiang, Gonglingxia; Xu, Qiangsheng; Tang, Jinli; Li, Xiaoli; Wen, Jiemei; Liu, Huimin; Tang, Chaowu; Dong, Ke; Kang, Zhenjun (Frontiers in Microbiology, 2020)
Phaeocystis globosa blooms are recognized as playing an essential role in shaping the structure of the marine community and its functions in marine ecosystems. In this study, we observed variation in the alpha diversity and composition of marine free-living bacteria during P. globosa blooms and identified key microbial community assembly patterns during the blooms. The results showed that the Shannon index was higher before the blooming of P. globosa in the subtropical bay. Marinobacterium (γ-proteobacteria), Erythrobacter (α-proteobacteria) and Persicobacter (Cytophagales) were defined as the most important genera, and they were more correlated with environmental factors at the terminal stage of P. globosa blooms. Furthermore, different community assembly processes were observed. Both the mean nearest relatedness index (NRI) and nearest taxon index (NTI) revealed the dominance of deterministic factors in the nonblooming and blooming periods of P. globosa, while the bacterial communities in marine waters after the blooms tended to be controlled by stochastic factors. Our findings revealed that the assembly of the bacterial community in marine P. globosa blooms is complex process with a mixture effects of marine microbiomes and environmental parameters.